Exploring the Influence of the Merdeka Curriculum on Elementary Students’ Moral Development - Ariswan; Neviyarni; Zelhendri Zen (Universitas Ahmad Dahlan, 2026)
This article aims to analyze the impact of the implementation of the Merdeka Curriculum on the moral development of elementary school students. The Merdeka Curriculum, which emphasizes flexibility, relevance, and student-centered learning, is expected to contribute positively to the development of students’ character and moral values. This study employs a literature review method to examine the concept of the Merdeka Curriculum, theories of moral development in elementary school children, and the potential relationship between the curriculum and students’ moral growth. The findings indicate that the flexibility of the Merdeka Curriculum enables teachers to integrate moral values contextually and in accordance with students’ needs. In addition, project-based learning and collaborative activities have the potential to foster empathy, responsibility, and social awareness among students. However, effective implementation requires teachers to possess a deep understanding of children’s stages of moral development as well as appropriate instructional strategies. The implications of this study suggest that elementary school teachers and educational policymakers should strengthen the integration of character education and ethical digital literacy within the learning process. Furthermore, schools are encouraged to design learning activities that promote students’ moral reasoning, collaboration, and social responsibility through meaningful real-life experiences. In conclusion, the Merdeka Curriculum has significant potential to support the moral development of elementary school students. Nevertheless, its success largely depends on well-planned and adaptive implementation practices.